OLIVEIRA, Francisco (Coord.), Penélope e Ulisses, Associação Portuguesa de Estudos Clássicos, Instituto de Estudos Clássicos, Centro de Estudos Clássicos e Humanísticos, Coimbra, 2003. - Maria João Botelho Moniz da Silva Marques (Ágora, 2004)
Sem resumo disponível.